Nutritional status and function after high-calorie formula vs. Chinese food intervention in undernourished children with cerebral palsy - Zhao, Yiting; He, Lu; Peng, Tingting; Liu, Liru; Zhou, Hongyu; Xu, Yunxian; Yang, Xubo; Huang, Yuan; Chen, Zhaofang; Xu, Yi; Li, Jinling; Hou, Xiaohui; et al. (Frontiers in Nutrition, 2022)
Aim: In this study, we investigated the efficacy and safety of high-calorie formula versus Chinese daily food on nutritional status and gross motor function of the undernourished children with cerebral palsy (CP). Methods: In this prospective, assessor-blind, and randomized controlled trial, we recruited children (1-10 years) with CP and undernutrition according to the WHO and American Society for Parenteral and Enteral Nutrition criteria from the National Children's Medical Center for South Central Region in China. Participants were randomly allocated (1:1) to high-calorie formula or Chinese daily food diets group (control group) for 6 months. Indirect calorimetry was used to estimate energy requirements. We compared the nutritional status and gross motor function of participants in boths groups based on weight, height, z-scores (weight-for-age, height-for-age, weight-for-height, and BMI-for-age) and the Gross Motor Function Measure (GMFM), respectively, at baseline, 3-, and 6-months follow-up. In addition, the effective rate of nutritional intervention and adverse events were assessed. This trial is registered with www.chictr.org.cn, number ChiCTR2000033878. Results: From July 2020 to December 2021, a total of 119 participants were enrolled and randomized, and 110 participants completed the study (with 54 children in high-calorie formula group and 56 children in control group). After 6 months of treatment, the weight, height, z-scores (weight-for-height, weight-for-age and BMI-for-age) and GMFM of both groups were significantly improved (p < 0.05). There were significant differences in changes of weight, weight-for-age z-scores and GMFM between the two groups (p < 0.05). Over the study period, 16 children experienced at least one treatment-related adverse event [9 (16.7%) in the formula group, 7 (12.5%) in the control group], although no serious adverse event was noted. Conclusion: Nutritional intervention with high-calorie formula may be an effective and safe option in children with CP for improving undernutrition and gross motor dysfunction.